Islamic Education Approach: Fethullah Gulen's Perspective - Ahmad Maruf; Sumantri, Dwipa (Insight School Academy, 2023)
Introduction to The Problem : Ideal education is viewed as a comprehensive process that fosters the full development of human potential, particularly intellectual growth, within educational institutions like schools. It emphasises the transmission of knowledge, traits, and abilities from one generation to the next. Nevertheless, contemporary education is frequently regarded as being surpassed, tending towards dehumanisation, and being accessible solely to the majority. Contemporary school education sometimes fails to ensure equitable chances for all pupils, particularly those who do not fall under the classification of